Motivation in school physical education: practice reports to teachers to students of 3rd secondary education series of state network paulista - Paulo César Cedran; Chelsea Maria de Campos de Martins; Dulcinéia Conceição Ligeiro (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
In the current design of School Physical Education the figure of the teacher should represent the mediation between knoledge and the teaching-learning process. So, thinking about the importance of the role that Professional in motivating students to participate in physical education classes, this paper aims reporting these experiences in building a concepto f physical education to arouse student's interest in knowing it and the habito f practicing it. In this sense, our goal is to investigate and compare with schools in Pitangueiras/SP and Jaboticabal/SP cities, the motivational level of students in 3rd grade of High School in Physical Education classes, from the official curriculum implemented by the Department of Education of the State of São Paulo (ESS/SP) in 2008.